Indirect estimation of reference intervals for thyroid parameters using ADVIA Centaur XP analyser - Mirjanić-Azarić, Bosa (Journal of Medical Biochemistry, 2021)
Background: The aim of this study was to determine the reference intervals (RIs) for thyroid stimulating hormone (TSH), free thyroxine (FT4), free triiodothyronine (FT3) and FT3/FT4 ratio using indirect methods.Methods: We analysed 1256 results TSH, FT4 and FT3 collected from a laboratory information system between 2017 and 2021. All measurements were performed on a Siemens ADVIA Centaur XP analyser using the chemiluminescent immunoassay. We calculated the values of the 2.5th and 97.5th percentiles as recommended by the IFCC (CLSI C28-A3).Results: The RIs derived for TSH, FT4, FT3 and FT3/FT4 ratio were 0.34-4.10 mIU/L, 11.3-20.6 pmol/L, 3.5-6.32 pmol/L and 0.21-0.47, respectively. We found a significant difference between calculated RIs for the TSH and FT4 and those recommended by the manufacturer. Also, FT3 values were significantly higher in the group younger than 30 years relative to the fourth decade (5.26 vs. 5.02, p=0.005), the fifth decade (5.26 vs. 4.94, p=0.001), the sixth decade (5.26 vs. 4.87, p˂0.001), the seventh decade (5.26 vs. 4.79, p˂0.001) and the group older than 70 years old (5.26 vs. 4.55, p˂0.001). Likewise, we found for TSH values and FT3 / FT4 ratio a significant difference (p
Keywords: reference intervals, indirect methods, thyroid parameters